Nilai Kognitif, Afektif dan Psikomotorik dalam Kisah Nabi Musa AS dan Nabi Khadir AS (Analisis QS. Surah al-Kahfi ayat 60-82) - Naf`an Rizal Syafi`ut Toriq; Ahmad Musta`in Syafi`ie (AS-SABIQUN, 2022)
This study aims to describe the cognitive values, affective values and psychomotor values contained in the story of Nabi Musa AS and Nabi Khadir AS in QS. al-Kahf: 60-82. This study uses a qualitative approach, the type of Library Research. This research is in the form of a study of verses, so that the primary data is the Qur'an, books of interpretation such as Ibn Kathir's interpretation, Munir's interpretation, al-Misbah interpretation, books of the stories of the Prophet and so on. The secondary data is from several literatures, such as books, journals, newspapers, and some notes that are still related to the research theme. The data collection method uses documentation techniques. While the data analysis used two steps, namely descriptive analysis and content analysis. The results of the study indicate that there are three domains of educational value in the story of Nabi Musa AS and Nabi Khadir AS in QS. al-Kahf: 60-82 as follows: First, detailed Cognitive Values are divided into six parts, namely: a) Knowledge, b) Chomprehension, c) Application, d) Analysis, e) Synthesis, and f) Evaluation. Second, the Affective Value is detailed into five parts, namely: a) Receiving, b) Responding, c) Valuing, d) Organization, and e) Characterization. Third, Psychomotor Values. Three actions taken by Khadir were punching holes in the boat, killing children and renovating walls.